Utilization and Uptake of Health Care Facilities by HIV Positive Antenatal Women Registered at PPTCT Centres of Surat City - Chauhan, Grishma D; Prasad, Rachana (National Journal of Community Medicine, 2018)
Background: HIV transmission from mother to child continues to be the major source of HIV infection in young children. This study assessed utilization and uptake of PPTCT services among HIV positive antenatal women registered at PPTCT centres of the Surat city. Materials and Methods: This Retro-prospective Cohort study en- rolled a sample of 282 HIV positive antenatal women registered for HIV testing and counseling during January 2007 to Dec 2008 in 5 PPTCT centres of Surat city and conducted from Dec 2008 to Nov 2010. Of these 127 (45%) antenatal women who came to collect their reports were included in the study and given post test coun- seling. Result: There was 55% loss to follow up among the HIV positive antenatal women and out of 127 (45%) women, 98(77%) had been registered in ART centres, from which only 45% started ART, 9% opted for abortion,105 (91%) were institutional delivery, among them only 38% underwent caesarean section,.101 (91%) mother- baby pairs received nevirapine prophylaxis at the time of labour and out of these, only 84 exposed babies were tested at 18 months of age and 5 (5.95%) were found to be positive among them. Conclusion: Utilization and uptake of PPTCT services among the HIV positive antenatal women has remained low even after avail- abilities of 5 PPTCT centres in the study area. Just like mothers, drop out in service utilization was observed among exposed children also.